Meta-Ethnography for Capacity Building: A Spiral Approach - Tan, Ai-Girl (Jurnal Pendidikan Bitara UPSI, 2022)
Graduate education aims to build capacities of current and prospective early childhood educators in conducting academic discourses which include among others reading, writing, and synthesizing studies published in academic journals and other credible sources. Academic writing can induce anxiety among graduate students (Bloom, 1982). It is thus important to teach, instruct and scaffold graduate education students in academic reading and writing and to develop capacities of graduate education students in proposing and conducting independent studies on the phenomena of their own interest. This paper focuses on introducing meta-ethnography and seven phases in an educational inquiry course of an early childhood graduate education programme. Teaching of qualitative synthesis in an inquiry course is designed in a spiral curriculum (Harden & Stamper, 1999) and is organized according to seven phrases (P) (Noblit, 2019): Getting started (P1), deciding what studies are relevant to that interest (P2), reading the studies (P3), determining how the studies are related (P4), translating the studies (P5), synthesizing the translations (P6), and expressing the synthesis (P6). The spiral approach to teaching meta-ethnography in inquiry comprises three stages: Getting ready for analysis (P1, P2, and P3 in iterations), getting ready for synthesis (P4 and P5 in iterations), and synthesizing and presenting the synthesis in academic writing (P6 and P7 in iterations). Within each stage, learning is spiral around four processes: Revisiting the topic or contents in the previous phase, increasing levels of difficulty, relating new learning to previous learning, and increasing competence.